2012
DOI: 10.1139/y2012-108
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine inhibits monocrotaline-induced pulmonary arterial remodeling involved in inhibition of RhoA–Rho kinase and Akt signalling pathways in rats

Abstract: Activation of the small GTPase Ras homolog gene family member A (RhoA) and Rho-associated kinase (ROCK) are important in the pathogenesis of pulmonary arterial hypertension (PAH). Selective serotonin reuptake inhibitors inhibit activation of RhoA and ROCK in vitro, and ameliorate PAH and pulmonary arterial remodeling in vivo. However, little is known about whether the RhoA-ROCK signalling pathway is involved in the treatment of PAH with fluoxetine in vivo. The aim of the present study was to investigate the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…Thus the present findings are supportive of a TG2-dependent mechanism since the SERT transporter would provide the intracellular 5-HT necessary for the serotonylation modification of AKT (Figure 7B). A role for SERT in AKT activation in vivo in a rat model of PH has been noted by others [29], and our findings here would indicate a TG2-mediated mechanism for this. An earlier report showed that 5-HT-driven AKT activation in PASMC was sensitive to 5-HT receptor (5-HTR) inhibitors [23]; however this was based on the use of only pharmacologic inhibitors, whereas the present study utilizes both pharmacologic and genetic inhibitions of SERT which support the concept that 5-HT-driven AKT also involves SERT.…”
Section: Discussionsupporting
confidence: 85%
“…Thus the present findings are supportive of a TG2-dependent mechanism since the SERT transporter would provide the intracellular 5-HT necessary for the serotonylation modification of AKT (Figure 7B). A role for SERT in AKT activation in vivo in a rat model of PH has been noted by others [29], and our findings here would indicate a TG2-mediated mechanism for this. An earlier report showed that 5-HT-driven AKT activation in PASMC was sensitive to 5-HT receptor (5-HTR) inhibitors [23]; however this was based on the use of only pharmacologic inhibitors, whereas the present study utilizes both pharmacologic and genetic inhibitions of SERT which support the concept that 5-HT-driven AKT also involves SERT.…”
Section: Discussionsupporting
confidence: 85%
“…Fluoxetine, is an inhibitor of SERT, and its inhibitory effects on pulmonary vascular remodeling in MCT-induced PAH are mediated through the downregulation of the ERK, Akt and RhoA/ROCK signaling pathways (17). In addition, fluoxetine suppresses lung tissue inflammation (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The data of pulmonary arterial pressure (PAP) and systemic arterial pressure (SAP) were kept as records under the same factors, as previously described (17,18). To measure PAP, a PV-1 catheter was inserted into the right jugular vein via the right atrium and ventricle, and was finally introduced into the pulmonary artery (16,18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental treatments that have been tested in this model include serine elastase inhibition (M249314 or ZD0892), platelet-derived growth factor inhibition (imatinib), Rhokinase inhibition (fasudil), endothelin receptor antagonists (endothelin-1), serotonin transporter inhibition (fluoxetine), phosphodiesterase-5 inhibition (sildenafil and phosphodiesterase-3/4 inhibitors such as pumafentrine), statins (simvastatin, pravastatin, and rosuvastatin), and many others. [53][54][55][56][57][58][59][60][61][62][63][64] The excessive degree of improvement with these experimental treatments has been criticized in the literature because it is believed to reflect imperfect models, inadequate duration of the studies, and endpoints that do not correlate with the progression of PH observed in humans. 26,27 Gomez-Arroyo et al 24 suggest that the MCT model harbors an MCT syndrome consisting of pulmonary interstitial edema, myocarditis, and hepatic veno-oclusive disease that is uncharacteristic of severe human PH.…”
Section: The Animal Models Used In Ph Research Monocrotaline Modelmentioning
confidence: 99%